Coach created motivational climate in professional tennis from the coaches` perspective: A qualitative study - Thorelli, E. G. (Norges Idrettshogskole, 2021)
This study explores professional Nordic tennis coaches` perceptions of the motivational climate they create to identify potential commonalities in their perceptions and differences in the perceived motivational climate. Hopefully, the results may inform coaches, players, sport directors, national federations, parents, and sport psychology consultants on how to build a sound motivational climate in professional tennis. Based on this intent, we answer the following research question: "How do professional Nordic tennis coaches on the ATP and WTA tours perceive the motivational climate created by themselves?" We explored eight elite tennis coaches` perceptions through semi-structured interviews. Due to the COVID-19 pandemic, seven out of eight interviews were conducted through Zoom meetings, and one was safely conducted face-to-face. We analyzed the data using a six-stage thematic analysis recommended by Braun and Clarke. Our findings show that the coach-created motivational climate in professional tennis was perceived by the coaches to be highly ego-involving; however, to handle this correctly, you should try to be mastery-involving as a coach and also as a player. According to the coaches interviewed, it is crucial to be your own coach as a player and to take massive ownership, focusing on personal development and executing maximum effort consistently. The results will eventually come, being the only thing that counts in professional tennis.